The difference between each number is 5:
- - -4 = 5
6-1 = 6
11-6 = 5
A)
The sequence formula is written using the first number in the sequence plus the difference times the term minus 1:
f(n) = -4 + 5(n-1)
b) replace n with 27 and solve:
f(27) = -4 +5(27-1)
= -4 + 5(26)
= -4 + 130
= 126
C)
replace f(n) with 124 and solve for x ( which is n in the equation):
124 = -4 +5(n-1)
Distribute :
124 = -4 + 5n - 5
Simplify:
124 = 5n- 9
Add 9 to each side:
133 = 5n
Divide both sides by 5:
n = 133/5
n = 26.6